THE N-HEXANE FRACTION OF MYRMECODIA PENDANS INHIBITS CELL SURVIVAL AND PROLIFERATION IN COLON CANCER CELL LINE - Bashari, Muhammad Hasan; Hidayat, Saras; Ruswandi, Yasmin Anissa Robles; Putri, Tenny; Qomarilla, Nurul; Dwiwina, Resti Gradia; Kurnia, Dikdik; Satari, Mieke H.; Huda, Fathul (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Despite advanced treatment options available for colorectal cancer, many reported resistance and unresponsiveness to conventional chemotherapeutic agents. Therefore, it is urgent to discover a novel drug for colon cancer. Sarang Semut (Myrmecodia pendans), an Indonesian native plant, has been studied extensively due to its anti-cancer profiles. This study aimed to evaluate the anti-tumour activity of Sarang Semut in colon cancer cells. Methods: We evaluated cytotoxic activity of methanol extract as well as n-hexane and ethyl acetate fraction towards colon cancer cell lines (Caco-2 and HCT-116 cells) utilizing 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay. The most potent fraction was evaluated further in inhibiting cell survival using MTT assay and cell proliferation using trypan blue exclusion assay as well as a clonogenic assay. Results: Our data showed that the n-hexane fraction of Sarang Semut induces more cell death than the methanol extract and ethyl acetate fraction. Therefore, we analyzed the n-hexane fraction further and found that the inhibitory concentration 50% (IC50) of the n-hexane fraction was 24 and 30 parts per million (ppm) for Caco-2 and HCT-116 cells, respectively. Moreover, it inhibited cell growth as well as cell colony formation, in particular, shown by the plating efficiency (P<0.05) and colony area per seed (P<0.01) of the control group were different to the treatment group. Conclusion: The n-hexane fraction of Sarang Semut demonstrates a high potential antitumor activity in colon cancer cell line.